2022
DOI: 10.1016/j.lana.2021.100130
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of non-natural manners of death in Ontario: Effects of the COVID-19 pandemic and related public health measures

Abstract: Background The effects of the COVID-19 pandemic on non-natural manners of death in Ontario is not known. Understanding the indirect consequences of the pandemic and related public health measures (i.e. lockdown) fills a vital need to inform best practice in public health and guide policy decisions. Methods The Office of the Chief Coroner and the Ontario Forensic Pathology Service (OCC-OFPS) investigate sudden and unexpected deaths in the province of Ontario. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“… 2 , 3 To illustrate, the increasing prevalence of major depressive and anxiety disorders in 2020 was positively related to the degree of pandemic seriousness in 204 countries 5 ; however, contrary to expectations, most studies from numerous countries reported that suicide mortality in 2020 did not increase, with the exceptions of Japan, India, Puerto Rico and Vienna (in Austria). 6 , 7 , 8 , 9 , 10 , 11 , 12 13 …”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 To illustrate, the increasing prevalence of major depressive and anxiety disorders in 2020 was positively related to the degree of pandemic seriousness in 204 countries 5 ; however, contrary to expectations, most studies from numerous countries reported that suicide mortality in 2020 did not increase, with the exceptions of Japan, India, Puerto Rico and Vienna (in Austria). 6 , 7 , 8 , 9 , 10 , 11 , 12 13 …”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability and use of extremely potent synthetic opioids has become a significant risk to public safety, resulting in 16,364 reported opioid-related deaths in Canada between January 2016 and March 2020 [ 5 ]. Furthermore, recent studies have shown an acute exacerbation of this accelerating trend of drug-related deaths throughout the COVID-19 pandemic, demonstrating an apparent compounding effect of the overlap of the opioid epidemic and COVID-19 pandemic in the drug-using population [ 6 ].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Fig 6. Number of acute drug toxicity deaths per year compared to the number of cases where naloxone was detected in acute drug toxicity death cases…”
mentioning
confidence: 99%
“…It is easily speculated that such deterioration in the psychosocial conditions of individuals would be correlated to increases in suicide mortality (1). However, unexpectedly, such increases in rates of suicide mortality were not observed in most upper-middle income countries/regions in 2020, with the exception of Japan and Vienna, Austria (7)(8)(9)(10)(11)(12)(13)(14)(15). Some countries even experienced decreases in the rates of suicide following the start of the pandemic.…”
Section: Introductionmentioning
confidence: 99%